A STUDY REGARDING THE LEVEL OF TRUST THE YOUNG ROMANIAN CONSUMER HAS IN PAID MEDIA AS OPPOSED TO THAT IN EARNED MEDIA - MIHAIL-CRISTIAN DIŢOIU (Challenges of the Knowledge Society, 2012)
Along with the evolution of the Internet and with its growing capacity to impose itself on the population, the consumer has become stronger through the simplification of access to information. Thus, 24 hours out of 24 hours, Internet users from all around the world are searching for relevant information about the product they desire. This is also the reason why organizations are striving to be as present as ever in the online medium, interacting with their consumers, monitoring the information dissipated by them on the Internet about their products, and measuring the effects they have produced. The media available to an organization is represented by: paid media, owned media and earned media. The problem that is raised is that of a correct management by the marketers so that the investment in one type of media will also pursue the conversion in another type of media, thus resulting, through the help of consumers, a chain. When a consumer wants to buy a product, he needs relevant information in order to make a decision. The information about the product is analyzed based on source credibility, which is seen as a perception of the degree of the consumer’s trust. The present study tries to investigate the level of trust the young Romanian consumer has in paid media and earned media during the buying process. The study is conducted on a group of young Romanian people, with ages ranging from 18 to 24 years, from urban backgrounds. In order to observe if there exists a difference in the perception of media based on the type of medium the subject finds himself in, the survey has been conducted online, as well as offline.